Ares : god of war - Temple, Teri.; Squier, Robert (Mankato, MN : Childs World, 2013)
An introduction to Greek mythology that shares the stories and myths about the Greek god Ares, god of war.
Includes bibliographical references (p. 32) and index.
Booklist
Library Media Connection
Booklist, January 2013
Library Media Connection, May 2013
5.4
Keywords: Ares (Greek deity) -- Juvenile literature; Mythology, Greek -- Juvenile literature; Ares (Greek deity); Mythology, Greek; Ares (Greek deity); Greek mythology